Characterization of Genome-Wide DNA Methylation and Hydroxymethylation in Mouse Arcuate Nucleus of Hypothalamus During Puberty Process - Yihang Shen (Frontiers in Genetics, 2020)
Background: Pulsatile pituitary gonadotropin secretion governed by hypothalamic gonadotropin-releasing hormone (GnRH) is essential for the pubertal onset. The epigenetic mechanism underlying the activation of GnRH-dependent regulatory axis in hypothalamus remains elusive. This study aims to explore the potential correlation between the signature of DNA (hydroxyl)methylation and pubertal process.Methods: Hypothalamic arcuate nucleus (ARC) of mouse at early (4-weeks) and late pubertal (8-weeks) stages underwent RNA-, RRBS-, and RRHP-seq to investigate the genome-wide profiles of transcriptome, differential DNA methylation and hydroxymethylation.Results: A series of differential expressed genes (DEGs) involved in sexual development could be separated into three subgroups with the significant difference of DNA methylation or hydroxymethylation or both in promoter regions. Compared to DNA methylation, DNA hydroxymethylation partook in more signaling pathways including synapse morphology, channel activity and glial development, which could enhance transsynaptic change and glia-to-neuron communication to faciliate GnRH release. The correlation between transcription and these epigenetic modifications indicated that DNA hydroxymethylation impacted with gene transcription independently of DNA methylation spanning puberty.Conclusion: Our results characterized the hydroxymethylation pattern and provided an insight into the novel epigenetic regulation on gene expression during pubertal process.